Business and management doctorates world-wide : developing the next generation - Palmer, Nicola J.; Davies, Julie; Viney, Clare (Emerald Publishing Limited, 2023)
The pursuit of excellence in business and management doctorates demands a delicate interplay between the capacity to synthesize intricate evidence (the ant hill) while maintaining a panoramic outlook (helicopter view) and crafting theoretical abstractions. Herein lies the challenge--maintaining equilibrium in this duality. Business and Management Doctorates World-Wide explores debates on the design and delivery of doctorates in business and management to support student employability and create impact. The book provides wide ranging international comparisons and reflections on the purpose and innovations in doctoral education offered by business schools today. Expert contributors analyze North and South American models, European doctorates, insights from the Arab World, doctoral provision in Australia and New Zealand, and ASEAN orientations. These global case studies incorporate explanations about the origins of existing systems and current drivers of behaviour, employment prospects for graduates, the opinions of different stake holders about the relevance of the programmes, and future emerging trends. Business and Management Doctorates World-Wide offers detailed comparative analysis of current practices to highlight reasons for commonalities and differences in different parts of the world with suggestions about lessons shared in diverse contexts.
Includes index.
Keywords: Degrees, Academic.; Business education.; Industrial management.; Business & Economics -- Education.; Business studies: general.; elektronické knihy; electronic books